SME food entrepreneurs and food crisis - Abu Samah, A’tiqah Rashidah; Ali, Noor Malinjasari; Abd Ghani, Roseziahazni; Mohamad, Zuraida; Ahmad, Zuriyati (Universiti Teknologi MARA, Terengganu, 2022)
Projection there may be food crisis facing our country Malaysia in the middle of this year raises public concern. Food crisis may affect the increase in prices of goods that can further increase the impact of inflation and affect our economy and the people. Moreover, the low value of the ringgit now also makes the prices of imported goods, including food, more expensive.